A Self‐Assessment Guide for Resident Teaching Experiences. Issue 6 (June 2016) - Engle, Janet P.; Franks, Amy M.; Ashjian, Emily; Bingham, Angela L.; Burke, John M.; Erstad, Brian L.; Haines, Seena L.; Hilaire, Michelle L.; Rager, Michelle L.; Wienbar, Rebecca
Abstract : The 2015 American College of Clinical Pharmacy (ACCP) Educational Affairs Committee was charged with developing a self‐assessment guide for residency programs to quantitatively and qualitatively evaluate the outcomes of resident teaching curricula. After extensively reviewing the literature, the committee developed assessment rubrics modeled after the 2013 ACCP white paper titled "Guidelines for Resident Teaching Experiences" and the revised American Society of Health‐System Pharmacists (ASHP) 2014 accreditation standards for PGY1 residencies, which place greater emphasis on the teaching and learning curriculum (TLC) than the previous accreditation standards. The self‐assessment guide developed by the present committee can serve as an assessment tool for both basic and expanded TLCs. It provides the criteria for program goals, mentoring, directed readings with topic discussions, teaching experiences, and assessment methodology. For an expanded TLC, the committee has provided additional guidance on developing a teaching philosophy, becoming involved in interactive seminars, expanding teaching experiences, developing courses, and serving on academic committees. All the guidelines listed in the present paper use the measures "not present, " "developing, " and "well developed" so that residency program directors can self‐assess along the continuum and identify areas of excellence and areas for improvement. Residency program directors should consider using this new assessment tool to measure program quality and outcomes of residency teaching experiences. Results of the assessment will help residency programs focus on areas within the TLC that will potentially benefit from additional attention and possible modification.